Biologics combined with conventional systemic agents or phototherapy for the treatment of psoriasis: real‐life data from PSONET registries. (17th October 2017) - Busard, C.I.; Cohen, A.D.; Wolf, P.; Gkalpakiotis, S.; Cazzaniga, S.; Stern, R.S.; Hutten, B.A.; Feldhamer, I.; Quehenberger, F.; Lichem, R.; Kojanova, M.; Adenubiova, E.; et al.
Abstract: Background: Biologics have greatly improved psoriasis management. However, primary and secondary non‐response to treatment requires innovative strategies to optimize outcomes. Objective: To describe the use of combined treatment of biologics with conventional systemic agents or phototherapy in daily clinical practice. Methods: We collected data on frequency of use, demographics, treatment characteristics and drug survival of biologics combined with conventional systemic agents or phototherapy in five PSONET registries. Results: Of 9922 biologic treatment cycles, 982 (9.9%) were identified as combination treatment. 72.9% of treatment cycles concerned concomitant use of methotrexate, 25.3% concerned concomitant UVB therapy, acitretin or cyclosporin and 1.8% concerned combined treatment with PUVA, fumaric acids or a second biologic. Substantial variation was detected in type and frequency of combination treatments prescribed across registries. Patients initiated on combined treatment had generally severe disease and were affected with psoriasis for many years. The extent to which patients had been priory treated with biologic monotherapy and the proportion of patients affected with psoriatic arthritis differed between registries. Survival rates for etanercept, adalimumab, infliximab and ustekinumab with methotrexate ranged between 43 and 92%, 28 and 83%, 65 and 87% and 53 and 77%, respectively, across registries after one year with no consistent superior survival for a particular biologic. Longest survival on a biologic combined with methotrexate, acitretin or cyclosporin was 103, 78 and 34 months, respectively. Conclusion: Methotrexate was the most commonly used concomitant treatment for patients on a biologic. Wide geographical variations in treatment selection and persistence of combination treatment exist. Data derived from ongoing studies may help to determine whether combined treatment is superior to biologic monotherapy.